2001
DOI: 10.1144/gsl.sp.2001.189.01.16
|View full text |Cite
|
Sign up to set email alerts
|

The modern water interface: recognition, protection and development — advance of modern waters in European aquifer systems

Abstract: Abstract:Modem groundwater that has recharged aquifers within the past 50 a shows the influence of humans globally, either by the presence of small concentrations of environmental tracers or in some cases by severe pollution. This study describes important environmental tracers (e.g. 3H, 85Kr, chlorofluorocarbons, SF6) and contaminants (e.g. NO3-, pesticides, chlorinated solvents) for modem groundwater dating and recognition of human impacts. Some applications of the described tracers in aquifers investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…Hence, for the majority of the major elements the composition of the Ribe Formation groundwaters is inherited from rainwater percolating through the Quaternary sands above undergoing carbonate dissolution and oxygen and nitrate reduction. No indicators of human impact (Hinsby et al 2001b) have been found in the Ribe Formation groundwater.…”
Section: Downgradient Hydrochemical Evolution In the Ribe Formationmentioning
confidence: 97%
“…Hence, for the majority of the major elements the composition of the Ribe Formation groundwaters is inherited from rainwater percolating through the Quaternary sands above undergoing carbonate dissolution and oxygen and nitrate reduction. No indicators of human impact (Hinsby et al 2001b) have been found in the Ribe Formation groundwater.…”
Section: Downgradient Hydrochemical Evolution In the Ribe Formationmentioning
confidence: 97%
“…Tracer methods are standard tools of hydrologists to obtain constraints on the age of groundwater and on processes and conditions water samples experienced during recharge and upon transit in the groundwater system (Plummer, 1993;Clark and Fritz, 1997;Cook and Herczeg, 2000;Hinsby et al, 2001;Loosli et al, 2001;Kooi, 2008a). In the following, key methods are summarised, and their potential for detecting temporal change in groundwater systems is discussed, focusing on relatively short time scales (less than 100 years).…”
Section: Age Dating and Chemical Proxiesmentioning
confidence: 99%
“…Application of radioactive and stable isotopes are useful tools for assessing human impacts on groundwater quality, e.g., through evaluation of groundwater residence times, pollution history and trends in groundwater bodies (Bohlke and Denver, 1995;Hinsby et al, 2001Hinsby et al, , 2007Visser et al, 2007), and for identification of different pollution sources (Aravena et al, 1993 etc. ).…”
Section: Introductionmentioning
confidence: 99%